Clinical characteristics of female Fabry disease patients with hypertrophic cardiomyopathy with mid-ventricular obstruction - Natsuko Inagaki; Yasuyoshi Takei; Tsuguhisa Hatano; Yasuyuki Takada; Yoshinao Yazaki; Hisanori Kosuge; Masatake Kobayashi; Shinji Suzuki; Tomohiro Umezu; Masahiko Kuroda; Kazuhiro Satomi; Takeharu Hayashi (Molecular Genetics and Metabolism Reports)
Fabry disease (FD) is an X-linked lysosomal storage disease caused by mutations in GLA, which encodes α-galactosidase A (GLA). The loss or reduced activity of GLA leads to damage to multiple organs, resulting in the intracellular accumulation of globotriaosylceramide in various organs, including the heart, kidneys, and nervous system. Pathological changes in the heart typically result in concentric left ventricular hypertrophy. Hypertrophic cardiomyopathy (HCM) is an intractable disease characterized by unexplained left ventricular hypertrophy and diastolic dysfunction and is typically characterized by asymmetric left ventricular hypertrophy. We performed a causative gene analysis in patients with a rare subtype of HCM, HCM with mid-ventricular obstruction (HCM-MVO), and identified four patients with different pathogenic variants of GLA, which were clinically confirmed as FD. All four patients with FD and rare HCM-MVO morphology were female, and all cases involved the classical form of the disease. Three cases in whom lymphocyte Lyso-Gb3 was measured showed a marked decrease in Lyso-Gb3 after initiating enzyme replacement therapy (ERT). However, even after ERT, myocardial involvement worsened in the long term, and two patients experienced fatal arrhythmias. Therefore, it is difficult to determine the efficacy of myocardial involvement in FD using a lymphocyte-based Lyso-Gb3 assay system. In addition, none of these female patients had renal dysfunction, indicating a different pattern of organ damage compared with that previously reported in male patients.